2007
DOI: 10.1021/jp0712405
|View full text |Cite
|
Sign up to set email alerts
|

Measurements and Quasi-Quantum Modeling of the Steric Asymmetry and Parity Propensities in State-to-State Rotationally Inelastic Scattering of NO (2Π1/2) with D2

Abstract: Relative integrated cross sections are measured for spin-orbit-conserving, rotationally inelastic scattering of NO (2Pi1/2), hexapole-selected in the upper Lambda-doublet level of the ground rotational state (j = 0.5), in collisions with D2 at a nominal energy of 551 cm-1. The final state of the NO molecule is detected by laser-induced fluorescence (LIF). The state-selected NO molecule is oriented with either the N end or the O end toward the incoming D2 molecule by application of a static electric field E in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…Van Beck et al 9 observed orientational effects in OH͑X 2 ⌸͒ -Ar rotationally inelastic collisions in a crossed beam experiment, and differential and integral cross sections for reorientation of the molecular axis were determined as a function of the initial orientation. Stolte and co-workers 10,11 investigated the steric asymmetry in rotationally inelastic collisions of NO͑X 2 ⌸͒ with several collision partners.…”
Section: Introductionmentioning
confidence: 99%
“…Van Beck et al 9 observed orientational effects in OH͑X 2 ⌸͒ -Ar rotationally inelastic collisions in a crossed beam experiment, and differential and integral cross sections for reorientation of the molecular axis were determined as a function of the initial orientation. Stolte and co-workers 10,11 investigated the steric asymmetry in rotationally inelastic collisions of NO͑X 2 ⌸͒ with several collision partners.…”
Section: Introductionmentioning
confidence: 99%
“…They were able to explain the remarkable fact that N-end (O-end) collisions are favoured for odd (even) changes in the rotational quantum number 16,19,26,27 . In addition, the existence of so-called parity pairs in the differential cross-sections was predicted by the QQT calculations and confirmed both experimentally and by exact quantum mechanical calculations.…”
mentioning
confidence: 98%
“…It has a phase part e iη i→f (γa;β) that will give the interference between the contributions from the different directions of the molecular axis. And it has a magnitude g geom (γ a ; β) = |g i→f (γ a ; β)| that, when squared, should be equal to the "classical" or "geometrical" differential cross-section for a fixed molecule, see also appendix C or equation (19):…”
Section: Theory Of Qqtmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparison, the reactivity of side on attack was found to be much smaller. 105 20 75 The effect of molecular alignment of metastable CO(a 3 Π 1 ) (created using optical electronic excitation of CO(X 1 Σ + , v = 0, J = 0) using linearly polarized light) with NO has also been investigated.…”
Section: Physical Chemistry Chemical Physics Accepted Manuscriptmentioning
confidence: 99%